Customer Attitudes towards A Public Sector Telecom Company (Bsnl) In Land Line - D Menon, Dr Sreeekumar (International Journal of Scientific Research and Management (IJSRM), 2016)
Customer attitudes are a composite of the three elements: cognitive information, affective informationand information concerning a consumer’s past behavior and future intentions. In other words attitudeconsist of thoughts or beliefs, feelings and behaviors or intensions towards a particular thing which caseis usually a good (concrete item) or service. Customers’ attitudes are highly important and evitable forthe smooth functioning of an organization having public dealing and responsibilities. It depends onseveral factors like tangibility, reliability, assurance, superior service quality, empathy etc. This paperstudied the various aspects of customer attitudes especially satisfaction, causes, reason, its impacts intelecom sector with suggestions. It is the main goal of every organization. Satisfaction level is a functionof difference between perceived performance and expectations. If the products’ performance exceedexpectation the customer highly satisfied or delighted. If the performance matches the expectation thecustomer is satisfied and if the product performance fall shorts of expectation the customer is dissatisfied.In the present scenario, the telecommunication is life blood for every business activities. It depends onseveral factors like tangibility, reliability, assurenc, superior service quality etc.